Intravenous catheter-related adverse events exceed drug-related adverse events in outpatient parenteral antimicrobial therapy. (20th November 2018) - Underwood, Jonathan; Marks, Michael; Collins, Steve; Logan, Sarah; Pollara, Gabriele
Abstract: Background: Drug-related adverse events (AEs) are reported to be common amongst patients receiving outpatient parenteral antimicrobial therapy (OPAT). However, comparative data regarding intravenous (iv) catheter-related AEs are lacking. Objectives: To compare drug- and iv catheter-related AEs from a large UK OPAT centre. Patients and methods: We reviewed 544 OPAT episodes [median (IQR) age: 57 (39–71) years, 60% male, 13% with diabetes] with a median (IQR) duration of 7 (2–18) days. Clinically significant drug- and iv catheter-related AEs were calculated as a percentage of OPAT episodes with an AE and also as AEs per 1000 iv drug/catheter days. Results: Drug-related AEs complicated 13 (2.4%) OPAT episodes at 1.7 (95% CI 0.9–2.9) per 1000 drug days. Catheter-related AEs occurred more frequently, complicating 32 (5.9%) episodes at 5.7 (95% CI 4.2–7.9) per 1000 iv catheter days ( χ 2 test for difference in AE rate: P  <   0.001). Non-radiologically guided midline catheters were associated with the most frequent AEs ( n  =   23) at 15.6 (95% CI 10.3–23.4) per 1000 iv catheter days compared with other types of iv catheters (HR 8.4, 95% CI 2.4–51.9, P  <   0.004), and self-administration was associated with a higher rate of catheter-related AEs at 12.0 (95% CI 6.0–23.9) per 1000 iv catheter days (HR 4.15, 95% CI 1.7–9.1, P  =   0.007). Conclusions: Clinically significant iv catheter-related AEs occurred more frequently than drug-related AEs, especially when using non-radiologically guided midline catheters. Regular review of the need for iv therapy and switching to oral antimicrobials when appropriate is likely to minimize OPAT-related AEs.